Serum amyloid A-mediated neuro-inflammation induces hippocampal neuron apoptosis and postoperative cognitive dysfunction in mice - Fu, Xiaochen; Cai, Zhenbin; Wu, Yuxuan; Xu, Yiwen; Gao, Ze; Tan, Minghui; Wang, Jing (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to explore whether serum amyloid A (SAA) triggers an inflammatory response by activating the NOD-like receptor protein 3 (NLRP3) pathway, resulting in hippocampal neuron apoptosis and cognitive impairments in mice.MethodsSAA was applied to BV-2 and HT22 cells to determine the optimal concentration and duration for stimulation. Inflammation-related and differentially expressed genes were identified through mRNA transcriptome sequencing (RNA-seq). Furthermore, apoptosis in hippocampal neurons was detected following treatment with the SAA-pretreated BV-2 cell culture medium. Furthermore, a postoperative cognitive dysfunction (POCD) mouse model was established using internal fixation of tibial fractures, followed by intraperitoneal injection of SAA and MCC950 (a selective NLRP3 inhibitor). Behavioral tests were then conducted to evaluate cognitive dysfunction in mice.ResultsmRNA transcriptome sequencing revealed that SAA led to the upregulation of inflammatory factors, including interleukin-1β (IL-1β). In cultured BV-2 cells, SAA treatment activated the NLRP3 signaling pathway. Additionally, the supernatants from SAA-treated BV-2 cells significantly increased the apoptotic rate in HT22 cells and primary hippocampal neurons. Pharmacological inhibition of NLRP3 using MCC950 reduced this apoptosis. The tibial fracture intramedullary nailing technique effectively established a mouse model of POCD, with SAA administration increasing inflammatory factor levels in the hippocampus of POCD mice and impairing their cognitive abilities. However, treatment with MCC950 significantly alleviated the cognitive dysfunction induced by SAA in the POCD mice.ConclusionSAA treatment triggers an inflammatory response through the activation of NLRP3, which subsequently causes hippocampal neuron apoptosis and impairs cognitive function in POCD mice. This dysfunction can be reversed by inhibiting NLRP3 with the administration of MCC950.